Determinação de carboidratos solúveis, redutores e não redutores, em cultivares de mandioca (Manihot esculenta Crantz) - de Battisti, Cremilda Rosa; Martins Batista, Cid; Teixeira Coelho, Dilson; Franco Feitosa Teles, Francisco; da Silveira, Américo José (Revista Ceres, 2025)
Levels of soluble reducing and non-reducing sugars (mono and disaccharides) were determined in the roots of 10 cultivars of cassava (Manihot esculenta Crantz). The highest levels of soluble reducing sugars were found in the cultivars ‘Sabara Entre Rios’ and ‘Branca de Santa Catarina’; however, the greatest amounts of soluble non-reducing sugars occurred in the cultivars ‘Pirassununga’ and ‘Manteiga’. The sugars were identified as fructose, glucose and sucrose.